Gambaran Penerimaan Diri Pada Perempuan Yang Pernah Mengalami Child Sexual Abuse Oleh Ayah - Marjono, Diyah Smara Annetta; Herdiana, Ike (Jurnal Ilmiah Wahana Pendidikan, 2025)
This study aims to understand the self-acceptance profile of women who wahe experienced Child Sexual Abuse by their father. The most severe form of Child Sexual Abuse is considered to be intrafamilial abuse, involving a father, uncle, or older brother. Such abuse leads to numerous negative impacts on the victims, one of which is low self-acceptance. The researcher seeks to explore further how vistims of Child Sexual Abuse by their father eventually achieve self-acceptance. This study employs a qualitative method with an intrinsic case study approach. There are two subjects involved in this research who are adult women over the age of 18 and have experienced Child Sexual Abuse committed by their father. Data collection for this study was conducted through interviews using the credibility member checking technique. Data analysis utilized a theory-driven thematic analysis technique. The results of the research indicate that initially, victims of Child Sexual Abuse by their father have low self-acceptance. However, they eventually manage to accept themselves by going through five stages: aversion, curiosity, tolerance, allowing, and friendship. Self-acceptance does not occur spontaneously but is facilitated by several factors, namely, a stable self-concept, favorable social attitudes, good childhood training, a preponderance of successes, and self-perspective.